Kilka uwag o diecie w świetle relacji łacińskich autorów patrystycznych i jej znaczeniu dla obrazu kondycji ekonomicznej społeczeństwa zachodniorzymskiego epoki późnego antyku - Wojcieszak, Maciej (Vox Patrum, 2025)
This article analyses the diet of late antique Western Roman society in the light of the texts of Latin patristic authors. The aim of this analysis was to demonstrate that the texts discussed diet data that can be used to reconstruct the image of the economic condition of society in the western part of the Roman Empire in the 4th and 5th centuries. There have been no attempts to study the works of Christian authors writing in the west of the Empire in this way. The biggest disadvantage of the used sources is that the analyzed authors created primarily didactic-pastoral literature, full of rhetorical figures and topos. They didn't mention pricing details, mostly just saying that the meal/ingredient was expensive/cheap. Nevertheless, if properly criticized, these texts are of great importance to the historian of late antiquity. Apart from the introduction and summary, the article is divided into three main parts: the diet of the upper classes of society, the diet of the lower classes of society, and the fasting diet. The main result of the conducted research is that, based on the diet of Western Roman society, we can cautiously state that the economic condition of the inhabitants of the western part of the Empire was neither dramatically bad nor exceptionally good, allowing people to live slightly above the minimum necessary for existence. The second conclusion is that, on the basis of the used sources, we can try to examine the economic condition of Western Roman society.